Investment decision-making process: heuristics and biases in South African based investment firms - Moyane, Sina Tracy (My University, 2018)
This research explores the heuristics and biases associated with investment decision-making in South African based firms. The key theoretical frameworks of the study investigate the impact that local and global financial, economic and political conditions have on investment decision-making. The key theoretical frameworks further explore the extent that heuristics and biases influence investment decision-making. Lastly, rationality and irrationality associated with investment decision-making is investigated. The research method follows a general inductive qualitative approach. The sample method is purposive heterogeneity sampling. The sample includes 20 investment decision-makers in the finance industry that are investing or specialise in investing in investments focused on the banking, financial services, asset management, construction, mining, defensive, credit, retail and industrial sectors, in Johannesburg, South Africa. There is extensive research on biases and heuristics, or preferences and judgements influenced by possible associations of personal preferences and beliefs. However, there is a lack of knowledge on the impact that heuristics and biases have on investment decisionmaking. Uncertainty within a given economy impacts investor psychology that results in heuristics and biases. Furthermore, the market in which investment decision-makers invest is also subject to heuristics and biases because the individuals that invest in the market possess personal biases and heuristics that drive market prices. Firstly, the research found that political instability, uncertainty and government actions influence investment decision-making. The research further found that perceptions have a significant impact on investment decision-making and the market in which they operate. Secondly, the research found that emotions, perceptions, experiences, ‘gut-feel’, cultural biases, uncertainty and past mistakes influence investor psychology and investment decisionmaking. Further, the main biases associated with investment decision-making include (i) familiarity bias, (ii) confirmation bias, and (iii) disposition effect bias. Thirdly, the research found that there are distinguishing characteristics between rational and irrational investment decision-making. The research indicated that investment decisionmaking associated with rationality mainly involves (i) a defined process, (ii) emotional separation and (iii) portfolio diversification. Irrationality associated with investment decisionmaking was found to be the opposite of rationality associated with investment decisionmaking. Therefore, this research investigates the extent to which heuristics and biases are associated with investment decision-making by investment decision-makers in Johannesburg, South Africa. The significance of this study is its contribution to the literature of management theory on heuristics and biases associated with investment decision-makers in firms based in Johannesburg, South Africa.
A research dissertation submitted to the School of Economic and Management Sciences, University of the Witwatersrand Johannesburg, in fulfillment of the requirements of a Masters of Commerce in Management Degree (100% Research). 2018